Factors Influencing Public Attitudes and Willingness to Utilize Telepharmacy Services in the UAE - Anan S. Jarab; Walid Al-Qerem; Tareq Mukattash; Ahmad Al-Azayzih; Zelal Kharaba; Shrouq Abu Heshmeh; Joud Al-Momani; Rama Hamdan; Yazid N. Al Hamarneh; Judith Eberhardt (International Journal of Telemedicine and Applications)
Conclusion: Forthcoming healthcare strategies should focus on expanding the availability of telepharmacy services throughout various regions of the country. This expansion will facilitate the broader utilization of these services and ultimately contribute to improved health outcomes.